Perkembangan Pembelajaran Sejarah Pasca Kemerdekaan-Reformasi - Ulfah Nury Batubara; Aman aman (Jurnal Pendidikan Sejarah, 2019)
Abstract: This article aims to examine the development of historical learning from post-independence Indonesia to the Reformation period. During that period, Indonesia has made 9 (nine) curriculum changes. Learning history at the beginning of independence was characterized by a spirit of nationalism, considering that this time, Indonesia still had to struggle to maintain its independence. Entering the Suharto government, historical learning directions and policies also changed along with political interests, namely strengthening the legitimacy of Suharto's power. Furthermore, the Reformation period marked by the end of Suharto's rule, the direction and purpose of historical learning also changed, namely preparing the younger generation to have human resources that are equal to other countries. Learning of the history of the reform era made many changes and reviewed various past events that did not exist in the history books of the New Order. The research method used is descriptive method, which describes the problem to obtain answers. The results of the study show that learning from time to time changes color following the color of government politics. This is because history learning has a very strategic role in supporting government programs. Artikel ini bertujuan untuk mengkaji perkembangan pembelajaran sejarah mulai dari pasca kemerdekaan Indonesia hingga masa Reformasi. Selama periode itu, Indonesia sudah melakukan perubahan kurikulum sebanyak 9 (sembilan) kali. Pembelajaran sejarah di awal kemerdekaan diwarnai dengan semangat nasionalisme, mengingat masa ini, Indonesia masih harus berjuang mempertahankan kemerdekaannya. Memasuki pemerintahan Soeharto, arah dan kebijakan pembelajaran sejarah juga berubah seiring dengan kepentingan politik, yakni memperkuat legitimasi kekuasaan Soeharto. Selanjutnya masa Reformasi yang ditandai dengan berakhirnya kekuasaan Soeharto, arah dan tujuan pembelajaran sejarah ikut berubah, yakni menyiapkan generasi muda untuk memiliki SDM yang sejajar dengan negara lain. Pembelajaran sejarah era reformasi banyak melakukan perubahan dan mengkaji berbagai peristiwa masa lalu yang tidak ada pada buku-buku sejarah masa Orde Baru. Metode penelitian yang digunakan adalah metode deskriptif, yaitu menggambarkan masalah untuk memperoleh jawaban. Hasil penelitian menunjukkan bahwa pembelajaran dari masa ke masa berubah warna mengikuti warna politik pemerintah. Hal ini disebabkan karena pembelajaran sejarah memiliki peran yang sangat strategis dalam mendukung program pemerintah.